Mixed methods evaluation of handshake antimicrobial stewardship on adult inpatient medicine floors - Elizabeth A. Neuner; Andrew Atkinson; Dan Ilges; Tamara Krekel; David J. Ritchie; Alice F. Bewley; Michael J. Durkin; Kevin Hsueh; Sena Sayood (Cambridge University Press, 2023)
Abstract Objective: To evaluate the effects of handshake antimicrobial stewardship on medicine floors at a large tertiary care hospital. Design: Retrospective observational study. Setting: 1,278-bed academic hospital. Patients: Adults admitted to non-ICU medicine services. Interventions: A handshake stewardship team consisting of an infectious diseases (ID) physician and pharmacist reviewed charts of patients receiving antimicrobials on medicine floors without a formal ID consult. Recommendations were communicated in-person to providers and acceptance rates were examined with descriptive statistics. Additional data regarding program perception among providers were obtained via surveys. Antibiotic usage trends were extracted from National Healthcare Safety Network Antimicrobial Use option data and evaluated using an interrupted time-series analysis pre- and post-intervention. Results:The overall acceptance rate of interventions was 80%, the majority being recommendations either to discontinue (37%) or de-escalate therapy (28%). Medical residents and hospitalists rated the intervention favorably with 90% reporting recommendations were helpful all or most of the time. There was a statistically significant decrease in vancomycin (78 vs 70 DOT/1,000 d present (DP), p = 0.002) and meropenem (24 vs 17 DOT/1,000 DP, p = 0.007) usage and a statistically significant increase in amoxicillin-clavulanate usage (11 vs 15 DOT/1,000 DP, p < 0.001). Overall antibiotic usage remained unchanged by the intervention, though pre-intervention there was a nonsignificant overall increasing trend while post-intervention there was a nonsignificant decreasing trend in overall usage. There was no change in in-hospital mortality. Conclusion: The addition of handshake stewardship with adult medicine services was favorably viewed by participants and led to shifts in antibiotic usage.